Tamil diaspora : intersectionality of migration, religion, language and culture - Vethanayagamony, Peter (New Delhi, Serials Publications, 2020)
Tamil Diaspora presents the fascinating saga of Tamil people around the world, a long and multifaceted history of their journeys, wanderings, triumphs and challenges on different shores of the world far from their ancestral homeland even as they adopt and adapt into their host countries. This volume is a brief snapshot of that complex narrative and explores the various dimensions of their lives in diaspora from diverse disciplinary lenses.
Keywords: Emigration and immigration; India, Tamil Nadu; Tamil diaspora; Sri Lanka.-- Emigration and immigration; Tamil (Indic people).-- Foreign countries; Tamil Nadu (India).-- Emigration and immigration; Conference papers and proceedings